2013
DOI: 10.1073/pnas.1305980110
|View full text |Cite
|
Sign up to set email alerts
|

A positive feedback loop links circadian clock factor CLOCK-BMAL1 to the basic transcriptional machinery

Abstract: Circadian clocks in mammals are built on a negative feedback loop in which the heterodimeric transcription factor circadian locomotor output cycles kaput (CLOCK)-brain, muscle Arnt-like 1 (BMAL1) drives the expression of its own inhibitors, the PERIOD and CRYPTOCHROME proteins. Reactivation of CLOCK-BMAL1 occurs at a specific time several hours after PERIOD and CRYPTOCHROME protein turnover, but the mechanism underlying this process is unknown. We found that mouse BMAL1 complexes include TRAP150 (thyroid hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 39 publications
1
79
1
Order By: Relevance
“…Alternatively, given that our results were obtained in a cellular context rather than in vitro chemical shift perturbation studies (14), it is possible that additional coactivators bound to dpCLK: dpBMAL1 also compete with dpCRY2 for binding. Histonemodifying enzyme orthologs of MLL and JARID1a, which are recruited at CLOCK:BMAL1, or proteins that recruit the transcriptional machinery are all potential candidates (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, given that our results were obtained in a cellular context rather than in vitro chemical shift perturbation studies (14), it is possible that additional coactivators bound to dpCLK: dpBMAL1 also compete with dpCRY2 for binding. Histonemodifying enzyme orthologs of MLL and JARID1a, which are recruited at CLOCK:BMAL1, or proteins that recruit the transcriptional machinery are all potential candidates (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that Thrap3 could interact with PPARg, and Thrap3 expression was required for adipose differentiation (Katano-Toki et al 2013). More recent studies have demonstrated that Thrap3 is a selective transcriptional coactivator for CLOCK-BMAL1, a common circadian clock factor, and depletion of Thrap3 causes low-amplitude, long-period circadian rhythms, identifying it as a positive clock element (Lande-Diner et al 2013). In addition, it has been reported that phosphorylation of PSF/SFPQ by glycogen synthase kinase 3 (GSK3) promotes an interaction with Thrap3 and prevents PSF from binding to the CD45 promoter (Heyd and Lynch 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thrap3 specifically interacted with wild-type PPARg following TNF-a treatment but was not observed in association with PPARg S273A in cells treated with TNF-a. Thrap3 is known to be a coregulatory protein that is loosely associated with the Mediator complex (Fondell et al 1996;Ito et al 2002) and is also reported to regulate several transcription factors (Lande-Diner et al 2013). Thrap3 is therefore a plausible candidate for involvement in phosphorylation-mediated PPARg regulation.…”
Section: Identification Of Thrap3 Binding To Phosphorylated Ppargmentioning
confidence: 99%
“…7D). THRAP3 has recently been identified as a coactivator of the CLOCK-BMAL1 complex and promotes its binding to target genes, linking it with the transcriptional machinery (38). This category also included the methyltransferase transcript MLL3, and the expression profiles of several transcripts associated with methylation are affected by mistimed sleep (Fig.…”
Section: Transcripts and Associated Processes Driven By The Sleep-wakmentioning
confidence: 99%